Sistem Informasi Manajemen Pemesanan Barang Menggunakan Delphi 2010 dan MySQL di Percetakan Rofi Graphis Kota Sukabumi - Herlina (BUANA INFORMATIKA CBI, 2019)
During this time, Rofi Graphis still uses a simple technology system in recording, compiling and storing order transaction data,such as recording order transactions in order data books, writing on an order letter and notes as proof of order and proof oftransaction and recording monthly reports on a books, sometimes just limited to being remembered. Because company owners consider the current system easier and does not interfere with existing work The author will try to make information system for ordering goods data management, with a system that the author makes and computerized using the Delphi2010 programming language and MySQL database, and help the admin / owner's work in managing data on sales and purchase of goods. The author analyzes existing data sources for making systems, designing inputs and outputs according to the analysis carried out, making program forms and codes so that they become the desired program.